1969
DOI: 10.1111/j.1365-2621.1969.tb12075.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Survivor Curves of Bacillus subtilis Spores Subjected to Wet and Dry Heat

Abstract: SUMMARY: Survivor curves for spores of Bacillus subtilis were determined in wet and dry heat over a wide range of temperatures. Wet heat tests were determined using a thermoresistometer and thermal death time cans. Dry heat tests were conducted in a closed system using thermal death time cans. There were major differences in the shape of the wet vs. dry heat survivor curves. Wet heat resulted in convex curves at low temperatures, but a straight line at higher temperature. Dry heat resulted in concave curves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

1972
1972
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 18 publications
1
16
0
3
Order By: Relevance
“…In fact, experiments on brief heating to more than 100°C of typical samples of MS-2 coliphage spores and Bacilus subtilis bacteria placed in vacuum on the back side of a thin metal biologically neutral target illuminated by a laser beam showed that they can survive these and even higher temperatures (Adushkin, 2005). In accordance with the data of other analogous investigations (Fox and Eder, 1969;Nicholson et al, 2000), it has been inferred that the probability of bacterium survival, which turned out to be weakly dependent on the duration and regime of heating, sharply drops at temperatures above ~200°ë and becomes critical (at a level of ~10 -4 ) at maximal values of ~250°ë. These experiments can be brought into correlation with the heating regimes of particles smaller than 10 µm in diameter entering the Earth's atmosphere.…”
Section: Collisions Of Dust Particles With Terrestrial Planetssupporting
confidence: 87%
“…In fact, experiments on brief heating to more than 100°C of typical samples of MS-2 coliphage spores and Bacilus subtilis bacteria placed in vacuum on the back side of a thin metal biologically neutral target illuminated by a laser beam showed that they can survive these and even higher temperatures (Adushkin, 2005). In accordance with the data of other analogous investigations (Fox and Eder, 1969;Nicholson et al, 2000), it has been inferred that the probability of bacterium survival, which turned out to be weakly dependent on the duration and regime of heating, sharply drops at temperatures above ~200°ë and becomes critical (at a level of ~10 -4 ) at maximal values of ~250°ë. These experiments can be brought into correlation with the heating regimes of particles smaller than 10 µm in diameter entering the Earth's atmosphere.…”
Section: Collisions Of Dust Particles With Terrestrial Planetssupporting
confidence: 87%
“…The mechanisms whereby wet heat inactivates spores more than dry heat have not been fully characterized, although it is not through DNA damage (22). It has been reported that the number of viable B. subtilis spores declined by more than 99% after 2 days of exposure to wet heat at 77°C (6). In addition, it has been shown, that vegetative Bacillus organisms are even more sensitive to wet heat, being inactivated at temperatures that are 30 to 40°C lower than those for spores (8).…”
Section: Discussionmentioning
confidence: 99%
“…The shape of all survival curves of bacterial spores exposed to IRH treatment was an upward convex, whereas concave survival curves have often been obtained by dry heat sterilization (Fox and Pflug, 1968;Fox and Eder, 1969;Murrell and Scott, 1966). Appearance of these nonlinear parts in the survival curve often leads to a misestimation of the total treatment time required for spore inactivation, because the simple logarithmic curve has been traditionally applied to the prediction of survival.…”
Section: Microorganismsmentioning
confidence: 99%